Three views of a saleroom. Valorization in and valuation of visual artworks by (mostly) Watteau, Altman and Banksy - Michael Hutter (Journal for Art Market Studies, 2021)
In the European tradition, markets have usually been represented as the place where the actual, live exchanges take place. The article therefore focuses on saleroom representations. These affect their own artistic value in two ways, leading to two questions: in a first move, the saleroom is an artistic device. How does the artist, or those who collaborate in creating an artwork, use references to a saleroom in order to put value into the work, to enrich it and thus contribute to its valorization? In a second move, spectators attribute value to the work, and they assess its value in comparison with that of other, similar works, and they pay money to possess works. How do they react to the use of the saleroom, what part does it play in their valuation of a particular work? To explore these questions, three works were selected: Antoine Watteau's Shopsign of the art dealer Gersaint is a fictitious version of the dealer's showroom; Robert Altman's film Vincent and Theo opens with the Christie's auction sale of one of Van Gogh's Vase with sunflowers paintings and goes on to recapitulate the relationship between Vincent and his brother Theo; Banksy's 2006 canvas version of Girl with Balloon, half-shreddered during its Sotheby's auction sale and renamed Love is in the Bin, was applauded as the first artwork to be created during an auction event. Salerooms, however, show only one part of art markets. The conditions of production as well as the drives that shape consumption remain unnoticed. They would require other forms of representation and conceptualization. Salerooms are also an unlikely conceptual device to show features of political domination. And yet, the three works contain quite explicit references to this sphere of value.
Keywords: 300